Turkey : Fifth Review and Inflation Consultation Under the Stand-By Arrangement, Request for Waiver of Nonobservance and Applicability of Performance Criteria, Modification of Performance Criteria, and Rephasing of Purchases; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Turkey. (IMF Staff Country Reports; Country Report, 2007)
Turkey's Fifth Review and Inflation Consultation under the Stand-By Arrangement and a Request for Waiver of Nonobservance and Applicability of Performance Criteria are discussed. Despite sharply higher interest rates, a weaker lira, and lower asset prices, economic activity has remained robust and foreign direct investment inflows buoyant. Balance sheets have also proven resilient. Achieving efficiency gains in the provision of health services and strengthening tax enforcement are crucial for the sustainability of public finances.